Inflamm-Aging Is Associated with Lower Plasma PTX3 Concentrations and an Impaired Capacity of PBMCs to Express hTERT following LPS Stimulation - Slusher, Aaron L.; Zúñiga, Tiffany M.; Acevedo, Edmund O. (Mediators of Inflammation, 2019)
Age-related elevations in proinflammatory cytokines, known as inflamm-aging, are associated with shorter immune cell telomere lengths. Purpose. This study examined the relationship of plasma PTX3 concentrations, a biomarker of appropriate immune function, with telomere length in 15 middle-aged (40-64 years) and 15 young adults (20-31 years). In addition, PBMCs were isolated from middle-aged and young adults to examine their capacity to express a key mechanistic component of telomere length maintenance, human telomerase reverse transcriptase (hTERT), following ex vivo cellular stimulation. Methods. Plasma PTX3 and inflammatory cytokines (i.e., IL-6, IL-10, TGF-β, and TNF-α), PBMC telomere lengths, and PBMC hTERT gene expression and inflammatory protein secretion following exposure to LPS, PTX3, and PTX3+LPS were measured. Results. Aging was accompanied by the accumulation of centrally located visceral adipose tissue, without changes in body weight and BMI, and alterations in the systemic inflammatory milieu (decreased plasma PTX3 and TGF-β; increased TNF-α (p≤0.050)). In addition, shorter telomere lengths in middle-aged compared to young adults (p=0.011) were negatively associated with age, body fat percentages, and plasma TNF-α (r=−0.404, p=0.027; r=−0.427, p=0.019; and r=−0.323, p=0.041, respectively). Finally, the capacity of PBMCs to increase hTERT gene expression following ex vivo stimulation was impaired in middle-aged compared to young adults (p=0.033) and negatively associated with telomere lengths (r=0.353, p=0.028). Conclusions. Proinflammation and the impaired hTERT gene expression capacity of PBMCs may contribute to age-related telomere attrition and disease.